Selenium fertilization enhances carotenoid and antioxidant metabolism to scavenge ROS and increase yield of maize plants under drought stress - Gorni, Pedro Henrique [UNESP]; Rodrigues, Cleverson [UNESP]; Spera, Kamille Daleck [UNESP]; Correia, Ricardo Francisco Ciaramicoli Cândido [UNESP]; Mendes, Nandhara Angélica Carvalho [UNESP]; Reis, André Rodrigues dos [UNESP] (Elsevier, 2025)
Water deficit (WD) is a phenomenon increasingly in different regions worldwide impacting agricultural production and food security. Selenium (Se) fertilization can help mitigate stress in plants, promoting greater resistance to adverse conditions, this element acts as an antioxidant, protecting plant cells from damage caused by environmental stress. This study aimed to evaluate the benefit effect of Se against WD by regulating metabolic responses. In a pot experiment, maize seedlings (V3 phenological stage) were exposed to WD (50%) and foliar application of Se at 50 g ha−1. Maize seedlings not exposed to WD or Se were used as controls. Exposure of maize seedlings to WD-Se resulted in a decrease in sugar, starch, and amino acid concentrations, negatively affecting size, diameter, and cob weight and in the weight and grain yield. However, WD + Se showed increases in total carotenoid and antioxidant metabolism resulting in higher growth parameters and yield of maize plants. Selenium supplementation at 50 g ha−1 increased leaf concentration of secondary metabolites, which, together with greater antioxidant activity non-enzymatic. Foliar Se application at low concentration and enhanced antioxidant metabolism promoting more tolerance to drought stress resulting in quality of grains and higher yield of maize plants under well-watered and WD conditions.
Keywords: Biofortification; Carotenoid metabolism; Drought stress; Grain quality; Secondary metabolites; Zea mays L.